Analysis of contents of annual sustainability reports of industrial companies participating in the sustainability index of the Brazilian Stock Exchange - Clemente, Ademir; Ribeiro, Flávio; Silva, Otávio Augusto de Paula da; Oliveira, Núbbia Mendonça (Revista de Administração da UFSM, 2020)
The objective of this article is to analyze the content of environmental disclosure of industrial companies participating in the Corporate Sustainability Index (ISE) of the Brazilian Stock Exchange (B3) from 2009 to 2016, based on the Stakeholders’ Theory perspective. We adopt a descriptive approach, with qualitative and quantitative analysis of secondary data that we analyze by means of content analysis and statistical techniques. The data collection took place from the institutional site of each organization to obtain the Annual Sustainability Reports. The reports went through text analysis, which resulted in an inventory of words related to the concept of sustainability. The results indicate that the analyzed companies have similarities with regard to the content disclosed in the Annual Sustainability Reports. Such similarities occur in spite of the fact that companies operate in different industrial segments (petrochemical, food, wood, pulp and paper products and personal use products) and probably come from a homogeneous perception of the segments interested in the information, which would be in reduced number. Although the surveyed companies operate in different segments, they are subject to similar pressures by stakeholders and that imposes an apparent homogeneity to their reports.